Nigerian Secondary School Teachers’ Attitudes Toward Including Students with Visual Impairments in Regular Classrooms - Ajuwon, Paul M; Shirley, Nora Griffin; Okungu, Phoebe; Chitiyo, George; Simone, Kinsey (International Journal of Rehabilitation and Special Education (IJRSE), 2025)
Using a questionnaire with open-ended survey items, this study used interpretivism to  understand Nigerian secondary school teachers’ perceptions of including students with  visual impairments (VI) in their classrooms, the availability of specialized resources,  and the adequacy of their training for effective inclusion. Findings revealed the general  education teachers had mixed feelings about the inclusion of children with VI due  to many challenges (e.g., lack of professional training, support, and resources). The  participants called for government support to assist with these challenges and to institute  changes in the official policy to provide better education for this population.
Keywords: secondary school teachers; attitudes; knowledge; inclusion; legislation; Nigeria